Theoretical, methodological and social potential in the final works of the Master Degree in Gynecological, Obstetric and Perinatal Nursing - Rojas Valenciano, Ligia (2015)
Introduction. The aim of this paper is to present the results of the research project No. 421-B2-A19 compared to the theoretical, social and methodological potential in the final works of the Masters Degree in Gynecological, Obstetric and Perinatal Nursing. The research component in an area of nursing, whose goal is to prepare professional clinical nurses about using research diligently.Method. Documentary research was applied as a variant of scientific research whose main objective is the analysis of different phenomena using very precise techniques of existing documentation, which directly or indirectly provide the information. 37 applied research projects, 22 in the qualitative approach and 15 in quantitative approach, from 2003 thru 2011. Each job was applied by using a critical analysis built from CASpe recomendations. We constructed a matrix for assessing documents of the quantitative approach (Critical Appraisal Skills Programme Spanish). For critical analysis of the final work of qualitative research, a matrix was also constructed using aspects of CAT (Critically Appraised Topic): EBCP (Evidence-Based Clinical Practice).Result. The final graduation work proved not prevailing in change or improvement of professional practice in terms of improving the quality of care given to people. They have only been relevant for a large group of postgraduate students. There is little clarity, in general, of the methodological aspects of both research approaches: qualitative and quantitative.Conclusion. Research Master Degree in Gynecologic, Obstetric and Perinatal nursing does not provide a substantive nursing knowledge, which leads to poor disciplinary development Final papers appear to be only a graduation requirement, which does not contribute to the improvement of Gynecologic, Obstetric and Perinatal nursing practices based on research